CHARACTERISTICS OF ARTIFICIAL INTELLIGENCE AS A TOOL OF INFORMATION MANIPULATION AND ITS IMPACT ON SOCIAL CONSCIOUSNESS - Davronov Bahodir Tohirjonovich (International Scientific and Current Research Conferences, 2025)
This article examines the emerging role of artificial intelligence (AI) technologies as instruments of information manipulation within the framework of a new communicative paradigm. The study explores how AI-driven algorithmic systems autonomously regulate the selection, dissemination, and contextual interpretation of information, thus posing significant challenges to objectivity, freedom of choice, and cognitive independence in social consciousness. Particular attention is paid to the philosophical, socio-psychological, and ethical dimensions of how algorithmic filtering on digital platforms, narrowing of cognitive fields, and construction of artificial narratives influence the formation and transformation of collective awareness. Furthermore, the paper critically analyzes the disruptive capacities of technologies such as deepfakes, generative neural networks, and automated bots, which blur the boundaries between truth and fabrication in digital environments, ultimately reshaping epistemological structures within society.